2013
DOI: 10.1080/09674845.2013.11669936
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of vancomycin-sensitive Staphylococcus aureus to subinhibitory levels of vancomycin leads to upregulated capsular gene expression

Abstract: Reduced vancomycin susceptibility in Staphylococcus aureus continues to trouble clinical microbiologists and infectious disease specialists. In this study, a vancomycin-susceptible S. aureus (VSSA) strain, which was methicillin-resistant (MRSA), was grown with and without subinhibitory levels of vancomycin, and the transcriptional profiles were determined by microarray analysis. Thirty-six genes were upregulated and 42 genes were down-regulated by more than two-fold (P< or =0.05) in the presence of vancomycin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Interestingly, vancomycin binds to D-alanyl-D-alanine and the active site of CarAB is very similar to that previously described for D-alanine:D-alanine ligase (Stapleton et al, 1996). In addition, carB was found to be the most highly induced gene in a vancomycin sensitive S. aureus strain when grown in the presence of vancomycin (Awad et al, 2013) and has previously been found to be involved in multiple cellular functions including biofilm formation and EPS formation (Zhuo et al, 2015). In STVAN20, we identified four SNPs with two occurring in promoter regions of different genes.…”
Section: Analysis Of Genetic Changes In Strains Resistant To Vancomycinsupporting
confidence: 78%
“…Interestingly, vancomycin binds to D-alanyl-D-alanine and the active site of CarAB is very similar to that previously described for D-alanine:D-alanine ligase (Stapleton et al, 1996). In addition, carB was found to be the most highly induced gene in a vancomycin sensitive S. aureus strain when grown in the presence of vancomycin (Awad et al, 2013) and has previously been found to be involved in multiple cellular functions including biofilm formation and EPS formation (Zhuo et al, 2015). In STVAN20, we identified four SNPs with two occurring in promoter regions of different genes.…”
Section: Analysis Of Genetic Changes In Strains Resistant To Vancomycinsupporting
confidence: 78%
“…Transcriptome profiles. Several of the selected articles employed a transcriptomic approach using microarray data analysis to study the effects of sub-MICs of antibiotics on staphylococcal virulence (44,45). This approach shares disadvantages with the quantitation of specific mRNA levels and may have decreased sensitivity for relatively small changes in gene expression.…”
Section: Readouts For Effects Of Antibiotics On Virulence Expressionmentioning
confidence: 99%
“…Nevertheless, this transcriptomic approach highlights some modifications in global metabolic pathways or regulatory systems but does not precisely measure any given virulence factor. With this method, Awad et al showed that a sub-MIC of vancomycin (1/2 MIC) induced upregulation of 36 genes of an epidemic MRSA strain, including 15 loci involved in cell wall metabolism, capsule, and autolysis, and downregulation of 12 loci with still-unknown functions (44). Similarly, Kuroda et al (45) showed that sub-MICs of cefoxitin induced the upregulation of several genes involved in the staphylococcal stress response and in the SaeRS regulatory system (discussed further in a later section).…”
Section: Readouts For Effects Of Antibiotics On Virulence Expressionmentioning
confidence: 99%